Inventory of Moss (Bryophyta) in Batang Gadis National Park, Mandailing Natal Regency as a Basis for Developing Contextual Biology Learning - Rizki Khairani Nasution; Latifah Hannum Siregar; Lidya Putri Solehan Rambe; Fatimah Ammarwiyah Dongoran; Aztri Ramadhani Harahap; Hasim Pajar Siregar; Reza Pahlevi (Bioedunis Journal, 2026)
This study aims to inventory the diversity of mosses (Bryophyta) in Batang Gadis National Park, Mandailing Natal Regency and analyze its potential as a basis for contextual biology learning in higher education. The study used a descriptive exploratory method through field surveys in several microhabitats, namely dense canopy forests, around streams, damp rocks, decaying wood, and forest paths. Data were collected through observation, morphological documentation, substrate recording, and sample identification. The results showed the discovery of 15 moss morphospecies consisting of mosses, liverworts, and hornworts. Habitats around streams have the highest diversity, while tree trunks are the dominant substrate. The diversity value is in the medium category, indicating that this area has microhabitats that support the growth of Bryophyta. The inventory results have the potential to be developed as learning resources in Lower Plant Botany, Plant Taxonomy, Plant Ecology, Biodiversity, and Conservation courses. This study contributes to the enrichment of local biodiversity data while supporting research-based biology learning and environmental potential.